Longitudinal Trend of Health-Related Quality of Life During Concurrent Chemoradiotherapy and Survival in Patients With Stage II–IVb Nasopharyngeal Carcinoma - Li, Ji-Bin; Guo, Shan-Shan; Tang, Lin-Quan; Guo, Ling; Mo, Hao-Yuan; Chen, Qiu-Yan; Mai, Hai-Qiang (Frontiers in Oncology, 2020)
Background and Aims To investigate the longitudinal trend of health-related quality of life (HRQOL) from the start to the end of concurrent chemoradiotherapy and survival in patients with advanced nasopharyngeal carcinoma (NPC). Methods A total of 145 patients with stage II–IVb NPC, who were a subsample of a randomized phase III clinical trial, were recruited in this study. HRQOL was measured weekly for a total of 6 weeks during concurrent chemoradiotherapy by the Chinese version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire core 30. Longitudinal trends of HRQOL domains over time were analyzed using mixed models. Survival rates were estimated using Kaplan-Meier method. Results During a median follow-up of 45 months, the 3-year progression-free survival rate, overall survival rate and distant metastasis-free survival rate were highly at 86.8% (95% CI: 80.1%, 91.4%), 95.1% (95% CI: 90.1, 97.6%), and 91.0% (95% CI: 84.9%, 94.6%), respectively. The average weekly declines of five functioning domains were 1.83 to 3.52 points during the treatment period, with role functioning having the largest decline rate (–2.52 points per week, 95% CI: –4.50, –2.55; p<0.001). Loss of appetite is the most affected symptom, with severe appetite loss ranging from 35.9% to 61.1%. The average increases of symptoms were 0.63 to 5.16 points per week during treatment period (all p values for time < 0.001, except for financial difficulties), with pain symptoms having the largest increase (5.16 points, 95%CI: 4.25, 6.08; p<0.001), followed by fatigue (3.62 points, 95%CI: 2.90, 4.35; p<0.001). Conclusion The HRQOL of patients with advanced NPC is poor and substantially deteriorated during the concurrent chemoradiotherapy (CCRT) period. Psychological care and support is necessary for patients with advanced NPC during the treatment period.